6(1-n)=6n+1

Simple and best practice solution for 6(1-n)=6n+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(1-n)=6n+1 equation:


Simplifying
6(1 + -1n) = 6n + 1
(1 * 6 + -1n * 6) = 6n + 1
(6 + -6n) = 6n + 1

Reorder the terms:
6 + -6n = 1 + 6n

Solving
6 + -6n = 1 + 6n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-6n' to each side of the equation.
6 + -6n + -6n = 1 + 6n + -6n

Combine like terms: -6n + -6n = -12n
6 + -12n = 1 + 6n + -6n

Combine like terms: 6n + -6n = 0
6 + -12n = 1 + 0
6 + -12n = 1

Add '-6' to each side of the equation.
6 + -6 + -12n = 1 + -6

Combine like terms: 6 + -6 = 0
0 + -12n = 1 + -6
-12n = 1 + -6

Combine like terms: 1 + -6 = -5
-12n = -5

Divide each side by '-12'.
n = 0.4166666667

Simplifying
n = 0.4166666667

See similar equations:

| 7x+1=2x-29 | | x*5+x=90 | | 2+6x=5x+7 | | 6x+6+4x=16 | | X+2=52-4x | | 2n^2+6n+8=0 | | 3x+12+2x+13=180 | | (7a-2)-(-3a+1)=-3(1-3a) | | z^2=-144 | | -2*(-2)= | | 2x+20+4x+10=180 | | 3x-7=79-3x | | 2.1x+49.6=15.4-9.3x | | 2*N*4=40 | | 8t-10=-18+6t | | yx=10 | | 8x-3=-57+2x | | 6*6+2y=12 | | 60+2x+3x=180 | | 15-b=a | | 4x=13x[]27 | | 6x+1=2x-19 | | 3(p-4)=8(p-4) | | D^2=-6d+27 | | 11x-4(x-5)=-22 | | 8=4-2x-4 | | x^2-5=-4x | | n+1=-11+3n | | x(15.5-x)=40 | | 4/2=5/b+10 | | 4+x=6x+39 | | b=a-15 |

Equations solver categories